THE ROLE OF ACADEMICIAN B. O. ORUZBAEVA IN THE STUDY OF KINSHIP TERMS (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
In the article, academician B. Oruzbaeva explained the etymology of the terms related to kinship in Kyrgyz linguistics and showed their sound structure into types, the opinions were analyzed. It was talked about the first phonetic features of scientific terms and how they were used in related languages, and by analyzing what phonetic features they have today, it was possible to reveal the historical creation, development process and historical reasons of languages. Although B. Oruzbaeva’s researches are not directly focused on kinship terms, words related to kinship are not only cited in her works, but also analyzed with their etymology. These mentioned issues indicate that Oruzbaeva is not indifferent to the issue of etymology, and that it is a necessary issue to have research in that direction.
Keywords: phonetic structure, related languages, kinship terms, etymology, Turkology, historical origin